The crisis-ridden capitalist mode of production as driving force for restructurations and transformations in and of the media industry : explanatory theoretical elements of a critique of the political economy of the media - Manfred Knoche (tripleC: Communication, Capitalism & Critique, 2019)
The goal of this article is to explain long term restructurations and transformations of the media industry. In order to do so, the article uses theory elements of a critique of the political economy of the media. The paper is a contribution to the development of theoretical approaches that provide a theoretical analysis of the media in capitalism based on Karl Marxs concepts. The capitalist mode of production is the primary driving force of media corporations' strategic action and of the media economys structural transformations. Factors that are of particular relevance in such structural transformations include profit orientation, capital accumulation, capitalist crises, state policies, behaviour of producers and consumers, private property, class relations, the antagonism between productive forces and relations of production, the antagonism of variable and constant capitalism, the antagonism of use-value and exchange-value, and competition. Competition, capitals need to survive, and capitalisms immanent crisis potentials force corporations try to create innovations such as new digital technologies. Informatisation, which includes the use of the computer as universal machine and the Internet, is the provisionally latest stage in the development of the productive forces that has affected media technologies and the media industry. The capital-driven structural digital transformation of the media industry has resulted in the convergence of production, distribution and consumption, the creation of a variety of non-tangible digital products, digital rationalisation and automation, and the universal real subsumption of labour under capital. These developments have also created the potential potentials for overcoming the capitalist character of the media economy and advancing decommodification based on the emergence of a universal digital media system.
Keywords: 330